Biological Composites Based on Fluoropolymers with Hydroxyapatite for Intramedullary Implants; Biomedical Engineering; Vol. 44, iss. 3 - Aronov A. M.; Bol’basov E. N.; Guzeev V. V.; Khlusov I. A. Igor Albertovich; Tverdokhlebov S. I. Sergei Ivanovich (2010, 2010)
Title screen